2012
DOI: 10.1556/aphysiol.99.2012.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antinociceptive potency of endomorphin-2 derivatives with unnatural amino acids in rats

Abstract: This study reports on the in vivo effects of four endomorphin-2 (EM-2) derivatives (EMD1-4) containing unnatural amino acids, i.e. 2-aminocyclohexanecarboxylic acid (Achc 2 ), para-fluorophenylalanine (pFPhe 4 ), β-methylphenylalanine (βMePhe 4 ) and/or 2',6'-dimethyltyrosine (Dmt 1 ). After induction of osteoarthritis by monosodium iodoacetate into the ankle joint of male Wistar rats, a chronic intrathecal catheter was inserted for spinal drug delivery. The mechanical threshold was assessed by a dynamic aesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For induction of osteoarthritis, rats were given a single intraarticular injection of 500 µg monosodium iodoacetate (MIA, Sigma-Aldrich Kft., Budapest, Hungary) in a volume of 50 μl through the infrapatellar ligament of the right hind knee using a 27-gauge needle 14,19 . Animals were left undisturbed for 14 days to develop mild cartilage destruction and osteoarthritis-like joint pain.…”
Section: Modeling Of Osteoarthritis and Cip Administrationmentioning
confidence: 99%
“…For induction of osteoarthritis, rats were given a single intraarticular injection of 500 µg monosodium iodoacetate (MIA, Sigma-Aldrich Kft., Budapest, Hungary) in a volume of 50 μl through the infrapatellar ligament of the right hind knee using a 27-gauge needle 14,19 . Animals were left undisturbed for 14 days to develop mild cartilage destruction and osteoarthritis-like joint pain.…”
Section: Modeling Of Osteoarthritis and Cip Administrationmentioning
confidence: 99%
“…β‐Methylphenylalanine (C 10 H 13 NO 2 ) is a non‐proteogenic and non‐natural amino acid with a molecular weight of 179.216 Da. β‐Methylphenylalanine has been shown to exert an antinociceptive effect in experimental animals, 10 and Ren et al 11 demonstrated that β‐methylphenylalanine exhibited anti‐arthritic activity in male albino rats. However, limited research is available on the biological effects of β‐methylphenylalanine.…”
Section: Introductionmentioning
confidence: 99%
“…The radiolabelled GTP analogue, [ 35 with free access to food and water, and with a 12:12 h light/dark cycle. Animal suffering and the number of animals per group were kept at a minimum; therefore, the drugs were administered in cumulative doses in 30-min intervals (at 0th, 30th and 60th min), and injections were repeated 7 days apart for the same animal, as in our previous study [169].…”
Section: Radiochemicalsmentioning
confidence: 99%
“…These injections did not elicit signs of major distress. Within 14 days MIA had consistently been shown to cause severe end-stage cartilage destruction resulting in osteoarthritis-like joint pain accompanied with moderate edema [169,175,176]. The observer was blind to the drug treatment administered.…”
Section: Chronic Inflammatory Pain Model and Measuring Allodyniamentioning
confidence: 99%